2016
DOI: 10.1111/ajt.13476
|View full text |Cite
|
Sign up to set email alerts
|

Proposed Diagnostic Criteria for Chronic Antibody-Mediated Rejection in Liver Allografts

Abstract: Donor‐specific alloantibodies (DSA) can cause acute antibody‐mediated rejection (AMR) in all solid organ allografts. However, long‐term outcome in patients with posttransplant DSA needs further study. We retrospectively evaluated prospectively collected paired serum, tissue, and data on 45 matched DSA− positive [DSA+; mean florescence intensity (MFI) ≥10 000] and ‐negative (DSA−) recipients of a primary liver‐only allograft from January 2000 to April 2009. Blinded histopathologic evaluation demonstrated that D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
120
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(124 citation statements)
references
References 54 publications
3
120
1
Order By: Relevance
“…179,180 There is increasing evidence that the formation of de novo DSAs in liver transplantation is an independent risk factor for graft loss. 39,181 Underimmunosuppression immediately after liver transplantation carries a higher risk of rejection. 158 Tacrolimus trough concentrations less than 7 ng/mL in the first week after liver transplantation is associated with higher rates of moderate/severe rejection compared with levels greater than 7 ng/mL.…”
Section: Evidence For Cni-minimization Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…179,180 There is increasing evidence that the formation of de novo DSAs in liver transplantation is an independent risk factor for graft loss. 39,181 Underimmunosuppression immediately after liver transplantation carries a higher risk of rejection. 158 Tacrolimus trough concentrations less than 7 ng/mL in the first week after liver transplantation is associated with higher rates of moderate/severe rejection compared with levels greater than 7 ng/mL.…”
Section: Evidence For Cni-minimization Strategiesmentioning
confidence: 99%
“…40 Liver transplant recipients were considered to be resistant to DSAs, so neither the presence of preformed DSAs or de novo DSAs was considered in the routine management of these patients. 263 Difficulties in characterizing acute AMR, a lack of a clear definition for chronic AMR, 181,264 and the lack of specificity of markers of complement activation (eg, C4d immunostaining) are some of the challenges in evaluating the role of DSAs in liver transplantation. 263 A large retrospective study has suggested an incidence of de novo DSAs at 1 year postliver transplant of 8%.…”
Section: Impact Of Antihuman Leukocyte Antigen Dsas In Kidney and LIVmentioning
confidence: 99%
“…The distinct morphology of the liver sinusoidal endothelium, with a larger luminal diameter, fenestrated endothelium, and lack of a basement membrane may confer its resistance to microvascular damage. Accordingly, most of the histopathologic evidence of AMR in the liver has been observed in the small vessels with continuous endothelia such as the portal microvasculature, hepatic arterial capillaries, and the peribiliary plexus [39, 40], not within the hepatic sinusoids.…”
Section: Perspectives On the Liver Allograft's Resistance To Antibmentioning
confidence: 99%
“…109 Diagnostic criteria for chronic AMR have recently been proposed for the identification of liver allograft recipients with DSA at higher risk for allograft loss. 117 When attempting to identify DSA+ patients at highest risk for overt problems, several factors have been elucidated. The quantity of alloantibody likely plays a role, in both preformed and de novo DSA at the population level, but, given the qualitative nature of current testing, this is difficult to pinpoint.…”
Section: Donor-specific Alloantibodies In Liver Transplantationmentioning
confidence: 99%
“…A small pediatric liver allograft study demonstrated that patients without DSA had the lowest risk of advanced fibrosis, those with either an HLA or angiotensin II type 1 receptor (AT 1 R) autoantibody had an intermediate risk, and all patients with both HLA DSA and AT 1 R antibodies developed advanced fibrosis. 111 In summary, patients at higher likelihood of developing progressive problems in the face of DSA posttransplant include those with: (1) a higher quantity of HLA DSA (which is difficult to measure with today's technology); (2) IgG3 subclass-positive DSA; (3) those with an additional injury, such as HCV infection, that can upregulate class II expression in the liver and thereby facilitate binding with crosslinking to allow injury to occur 117 ; and (4) possibly those with both HLA and non-HLA antibodies.…”
Section: Donor-specific Alloantibodies In Liver Transplantationmentioning
confidence: 99%